Comparison of Knowledge and Attitudes of Faculty of Nursing and Non-Faculty of Nursing Students of Indonesian Adventist University Toward Human Monkeypox - Nakluy, Mestrin Jois; Ernawaty Siagian (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
Effective disease control, including monkeypox (mpox), relies heavily on community knowledge and adherence to preventive measures. To compare the knowledge and attitude of Faculty of Nursing and Non-Faculty of Nursing students of Universitas Advent Indonesia towards Human Monkeypox. This study is descriptive and uses quantitative methods with a cross-sectional approach. Data were collected using a validated Google Form questionnaire. The population of this study consisted of students from the Faculty of Nursing and Non-Faculty of Nursing at Adventist University of Indonesia. Sample: The sample consisted of 120 students, with each group (Faculty of Nursing and Nursing) totaling 60 people. The results of this study showed that Nursing students had better knowledge and attitude toward Human Monkeypox than Non Nursing students. A total of 47 people (78%) had high knowledge and 55% had a good attitude, while in Non-Nursing only 38 (63%) had the level of knowledge and 4 people (7%). There is a significant difference with (P < 0.001), Knowledge and attitude of Faculty of Nursing students towards Human Monkeypox are better than Non-Nursing students. Based on the results of this study, it is recommended that higher education institutions develop interdisciplinary education related to infectious diseases such as Human Monkeypox. Education can be carried out through seminars, training, curriculum integration, and optimization of digital media. Collaboration between faculties is also important to strengthen literacy and preventive attitudes towards infectious diseases.